Comparative In Vitro Antifungal Activity of Amphotericin B and Amphotericin B Methyl Ester - Howarth, William R. (1975)
The in vitro antifungal activity of amphotericin B methyl ester (AME), a water-soluble derivative of amphotericin B, was compared to that of the parent compound against a variety of pathogenic and potentially pathogenic fungi. AME has a significant antifungal activity, but the activity of AME was slightly lower than that of amphotericin B. Among the yeast-like organisms, only the yeast cells of Sporothrix schenckii were more resistant than others to both antibiotics, with a minimal fungicidal concentration of 5 to 10 μg/ml. The yeast cells of other fungi were killed at concentrations of 1 μg or less of either antibiotic per ml. The filamentous forms of S. schenckii and Oidiodendron kalrai were more resistant than the filamentous forms of other dimorphic fungi to both drugs. The minimal fungicidal concentration for S. schenckii was 10 μg/ml and for O. kalrai, 50 μg/ml. The dermatophytes, phycomycetes, and dematacious and other potentially pathogenic fungi were inhibited fairly well by both drugs, but up to 50 μg/ml was required for fungicidal action. The water solubility and wide spectrum of antifungal activity of AME warrant evaluation of its chemotherapeutic activity against experimental fungal infections.